Criação de APAs no manancial de abastecimento público de Cianorte-PR: uma alternativa para a promoção do uso sustentável da bacia e a manutenção da qualidade do recurso hídrico - Silva, Marcio Santos da (2020)
This work analyzed the contribution that the creation of Environmental Protection Areas - APAs in the hydrographic basin of the Ligeiro River, involving the municipalities of Araruna and Cianorte (northwestern Paraná), can have for the conservation of water resources. This river will be used, from 2022, as a new source of public supply in Cianorte. As a methodological parameter, the study of APAs existing in the water sources of the Araras stream, in Paranavaí-PR and of the Piava river, in Umuarama-PR, was used. After analyzes carried out, through documents and interviews with managers, it was found that these APAs represented a significant advance in the conservation of water resources by the various actions implemented in the basins such as reforestation and the implementation of a fence in the Permanent Protection Area - APPs. From the study of these APAs, data and information surveys were made on the hydrographic basins of the current Cianorte spring in the Bolívar stream and the future spring, the Ligeiro river. It was found that the area of the Bolívar river source, which has 24.35 km² (from the source to the Gross Water Pumping Station - EEB-1), presents environmental problems and risks caused mainly by urban expansion and the practice inadequate soil management and use. Among the main problems are the degradation of APPs and the formation of erosive processes, which have caused silting and increased turbidity index due to the systemic relationship that exists between environmental components (rocks, soils, water, vegetation, relief and climate) ). This situation has already compromised the supply of the population in 2015 and still represents an imminent risk of a new occurrence, especially on days with high levels of precipitation. Still, there is the issue of the grant whose flow is less than the recommended. In relation to the Ligeiro River basin, the source area will have 429.58 km² from the source to the future EEB-2. In this area, some natural characteristics that favor the emergence of water erosion have been identified, such as the predominance of sandy soils, humid subtropical climate, slope that contributes to the flow of waters and erosive potential classified as very high to high. Through aerial images it was also possible to verify APP degradation points, inadequate use and occupation of the soil, presence of industries with potential for pollution, among others. Considering the need to conserve the waters of the future public water source in Cianorte, this study proposed the creation of two APAs in the Ligeiro River basin, one in the municipality of Araruna with an area of 209.76km² (left bank) and one in the municipality of Cianorte with an area of 219.82 km² (right bank). It is believed that the creation of these APAs may contribute significantly to the conservation of natural resources and, especially, of water resources in view of the water quality so that, in the future, the Ligeiro River does not have the same destination as the Bolívar stream.